Analisis Penerimaan Pajak Bumi Dan Bangunan Kecamatan Kotapinang Pada Badan Pengelolaan Pendapatan Daerah Kabupaten Labuhanbatu Selatan - Sri Rahayu; Yenni Samri Juliati Nasution; Laylan Syafina (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
The purpose of this study is the result of research to find out how effective the revenue from land and building tax in Kotapinang sub-district is at the regional revenue management agency for South Labuhanbatu Regency and to find out how the efforts made by the Kotapinang regional government in increasing land and building tax revenue. This study uses a qualitative method with a descriptive approach. In this study the authors conducted interviews with companies. And using two data, namely primary and secondary data. The results showed that the amount of land and building tax revenue in Kotapinang District at the South Labuhanbatu Regency Revenue Management Agency in 2018 was 23%, 2019 was 18%, 2020 was 21%, and 2021 was 32%. Efforts made by the Kotapinang regional government in increasing land and building tax revenues are by conducting outreach to taxpayers about the importance of paying taxes with the aim of growing taxpayer self-awareness to pay taxes. In addition, creating an e-tax application that can be accessed using a smartphone to make it easier for taxpayers to pay taxes.